Rapidly progressive kidney failure induced by fungal mycelia obstructing indwelling ureteral stents. (14th December 2012) - Dubert, Marie; Loi, Valeria; Tligui, Mohamed; Hertig, Alexandre
Abstract : Antibiotics reduce the commensal flora in the gut, thereby facilitating the overgrowth of undesirable microorganisms such as Candida albicans . Here, we report the case of a 48-year-old woman with a history of obstructive uropathy consecutive to a radiation therapy, in whom both indwelling ureteral stents were rapidly occluded by fungal mycelia, resulting in a rapidly progressive kidney failure. Ascendant infection by C albicans had occurred after a 2- week course of antibiotics, prescribed for a perforative peritonitis also due to radiation-induced colitis. As shown by iterative CT scans made before (at the time of the diagnosis of peritonitis) and after the antibiotic course, kidney failure was explained by a sudden and bilateral pyelocaliceal dilation, due to the obstruction of the ureteral stents. Fungal mycelia were objectivised during the replacement procedure. Intravenous fluconazole was started, and renal function recovered ad integrum with the relief of the obstruction.